Analisis Faktor Risiko Kejadian Hipertensi Pada Lansia Di Wilayah Kerja Puskesmas Rapak Mahang Kecamatan Tenggarong Kabupaten Kutai Kartanegara - Afifah, Wiwin Vidiyastana; Pakki, Irfansyah Baharuddin; Asrianti, Tanti (Wal'afiat Hospital Journal, 2022)
Hypertension is one of the non-communicable diseases that mostly affects people of productive age and the elderly today. Hypertension is called the silent killer because it is often without complaints, so the patient does not know he has hypertension, and prevention efforts cannot be carried out as early as possible with the causative factors of hypertension caused by several risk factors, one of which is based on the host/human. This study aims to determine the relationship of family history of hypertension, physical activity, obesity, and smoking to the incidence of hypertension in the Work Area of the Rapak Mahang Health Center. This type of research is analytic with a cross-sectional approach and the sampling technique is purposive sampling. Collecting data using a questionnaire with a number of respondents as many as 128 people. Data were analyzed using the chi-square test. The results of data analysis showed the frequency of hypertension sufferers among as many as 99 people (77.3%). The bivariate test showed statistically significant results between the variables of family history of hypertension (p-value = 0.003), obesity (p-value = 0.000), and physical activity (p-value = 0.019) with the incidence of hypertension. The smoking variable (p-value = 0.361) statistically showed no relationship with the incidence of hypertension. There is a relationship between a family history of hypertension, obesity, and physical activity with the incidence of hypertension and there is no relationship between smoking and the incidence of hypertension.